Sustainable Business Ethics: Fostering Corporate Responsibility and Environmental Stewardship - Wahyuni, Wahyuni; Ulfa, Fahriji; Novianti, Andi; Rosalinda, Rosalinda (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study aims to investigate how small and medium-sized enterprises (SMEs) can effectively integrate sustainable business ethics, corporate social responsibility (CSR), and corporate governance into their operations. The study explores how these elements contribute to long-term business sustainability despite the resource constraints often faced by SMEs. Research Design and Methodology: This research utilizes a qualitative systematic literature review, analyzing existing literature on sustainable business ethics, CSR, and governance, focusing on SMEs. The review identifies the interrelationship between ethical principles, stakeholder engagement, and governance structures in driving corporate sustainability. Findings and Discussion: The study reveals that SMEs can adopt sustainability practices by leveraging innovation, resource efficiency, and strong stakeholder relationships. It supports the hypothesis that ethical business practices are integral to achieving sustainability and competitive advantage. Furthermore, governance structures are essential for maintaining accountability and ensuring the effective implementation of sustainability initiatives. Implications: The research highlights the importance of governance frameworks and transparent reporting mechanisms for practical applications in strengthening stakeholder trust and enhancing business performance. The findings contribute to academic discussions on the role of SMEs in sustainability, offering actionable strategies for businesses to integrate ethical principles and sustainability practices even with limited resources.